2016
DOI: 10.5350/sleep.hypn.2016.18.0130
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Psychological and Family Factors Associated with Sleep Quality among Pregnant Women

Abstract: Objective: Given the significance of sleep quality among pregnant women and its effects on the health of the fetus and the lack of sufficient studies in this field as well, the present study aimed to both identify some of the psychological factors associated with sleep quality among pregnant women and investigate the relationship between sleep quality among pregnant women and other variables, including depression, anxiety, stress, resilience, perceived social support, and marital adjustment. Materials and meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
(57 reference statements)
0
4
0
2
Order By: Relevance
“…Pregnancy is a process accompanied by dramatic hormonal changes (1-3) that create significant anatomical, physiological, and biochemical changes in a woman's life. These hormonal changes can also have profound effects on women's ability to sleep and may result in poor sleep quality (4)(5)(6)(7). Sleep is a physiological process and a basic requirement for the physical and mental well-being of pregnant women and their fetuses (2,8).…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy is a process accompanied by dramatic hormonal changes (1-3) that create significant anatomical, physiological, and biochemical changes in a woman's life. These hormonal changes can also have profound effects on women's ability to sleep and may result in poor sleep quality (4)(5)(6)(7). Sleep is a physiological process and a basic requirement for the physical and mental well-being of pregnant women and their fetuses (2,8).…”
Section: Introductionmentioning
confidence: 99%
“…Majoriteten av forskningen som finns är kvantitativa studier och sammanfattningsstudier. Sex av studierna är gjorda i Asien (Effati-Daryani et al, 2016;Reshadat et al, 2018;Rezaei et al, 2013;Tsai et al, 2016;Zhong et al, 2018;Zhou et al, 2020). Fyra studier kom ifrån USA (Chang et al, 2010;Facco et al, 2010;Kalmbach et al, 2020;Mindell et al, 2015).…”
Section: Bakgrundunclassified
“…Sömnproblem under graviditet påverkade det psykiska måendet (Effati-Daryani et al, 2016;Kalmbach et al, 2019;Sarberg et al, 2019;Reshadat et al, 2018;Rezaei et al, 2013;Tsai et al, 2016;Ertmann et al, 2020). Sömnproblem ökade risken för depression och ångest under graviditeten (Kalmbach et al, 2019), samt postpartumdepression (Sarberg et al, 2016;Reshadat et al, 2018;Zhou et al, 2020).…”
Section: Bakgrundunclassified
“…Moreover, research has consistently shown that pregnant women with high resilience exhibit better-coping abilities in managing childbirth-related concerns and report lower levels of fear of childbirth [ 10 , 20 ]. Furthermore, resilience has been confirmed as a crucial protective factor for mental health and better sleep quality among pregnant women [ 18 , 21 23 ]. Thus, resilience may have an important role in the relationships among fear of childbirth, psychological distress, and sleep quality.…”
Section: Introductionmentioning
confidence: 99%